Agronomic practices affect rice yield and nitrogen, phosphorus, and potassium accumulation, allocation and translocation. (11th March 2020) - Lv, Yandong; Hu, Yue; Jiang, Hongfang; Lan, Yuchen; Wang, Heying; Xu, Lingqi; Yin, Dawei; Zheng, Guiping; Guo, Xiaohong
Abstract: Applying appropriate agronomic practices instead of conventional farming practices might improve rice yield. However, few studies have focused on how integrated agronomic practices affect N, P, and K accumulation and allocation in rice ( Oryza sativa L.). Therefore, this study was conducted to investigate grain yield, N, P, and K accumulation, and allocation under different agronomic practices. A japonica rice cultivar was grown in the field, with four agronomic practice treatments: no N application (N0), local farmers' practice (FP), high‐yield practice (HYP), and super‐high‐yield (SHY) practice. The results showed that the latter two practices significantly increased grain yield by 11.0% and 26.4%, respectively, compared with that under FP, mainly as a result of an increase in mean number of panicles m −2 and spikelets panicle −1 . Mean aboveground N, P, and K accumulation significantly increased by 24.9, 15.3, and 79.1%, in HYP and 42.0, 38.8, and 219.7% in SHY, respectively, compared with that under FP. In particular, K accumulation was higher than N and P accumulation in HYP and SHY plants than those in FP plants. However, N, P, and K grain productivity was lower by 7.5, 9.5, and 20.3% under HYP, and 20.3, 17.2 and 62.7% under SHY treatments than that of FP, respectively, and N, P, and K grain productivity were negatively correlated with yield. Our results suggest that an increase in N, P, and K accumulation from the full‐heading stage (FH) to the maturity stage (MS) may assist with improving rice yields under HYP and SHY treatments.